Scales for Assessment of Adolescents With Antisocial Behaviour - Džamonja-Ignjatović, Tamara; Hrnčić, Jasna; Žegarac, Nevenka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
The paper presents and analyses descriptive and metric characteristics as well as applicative potentials of several assessment scales for adolescents with antisocial behaviour. The purpose of scales is to assess personal characteristics of adolescents, their families and peer groups that present the relevant ground for planning, monitoring and evaluation of the effects of social services, mental health and psychological counselling services, schools’ programs, etc. The scales were developed through different projects and research and were empirically checked out in the adolescent population in Serbia. Assessment scales included were: Conflict Tactics Scale (TAKIT), Aggression Self Assessment Scale (SAG), Personal Believes Scale (LUS,) Self-Efficiency Scale (SES) and Peer Group Antisocial Behaviour Scale (POKS-R). Almost all scales showed high reliability and predictive validity. Only the SES scale showed lower reliability, due to the small number of items and heterogeneity of included aspects of self-efficacy. Considering the importance of self-efficacy in planning and evaluation of treatments of adolescents with antisocial behaviour, further modification of the scale is recommended.